Luminescence properties of Eu3+ activated Y2O3 red phosphor with incorporation of Ga3+ and Bi3+ trace hertero-cations in the Y2O3 lattice. (September 2018) - Yousif, A.; Abbas, Babiker H.; Kumar, Vijay; Pandey, Anurag; Swart, H.C.
Abstract: The luminescence characteristics of Eu 3+ doped Y2 O3 in the presence and absence of Bi 3+ /Ga 3+ trace ions prepared by the sol-gel combustion method were investigated. The results revealed that, the Bi 3+ and Ga 3+ ions have a significant influence on the excitation position and emission bands intensity of Eu 3+ doped Y2 O3 . The cathodoluminescence (CL) intensity of the Y2 O3 :Eu 3+ incorporated with Bi 3+ /Ga 3+ ions has been considerably enhanced (five times), compared to the CL intensity of the unincorporated Y2 O3 :Eu 3+ samples. This phenomenon was attributed to the energy exchange in the excitation bands of the Bi 3+ and Eu 3+ ions. Highlights: Y2 O3 :Eu 3+ with and without Bi 3+ /Ga 3+ ions were prepared. Bi 3+ and Ga 3+ ions have a significant influence on the excitation position. Considerably enhanced (five times) to the CL intensity and emission band intensity. Energy exchange in the excitation bands of the Bi 3+ and Eu 3+ ions occurred.